Estética afrofuturista: história, teoria e sua expressão no Brasil - Silva, Felipe Pereira da (2025)
"The world of tomorrow will be Africa" (MBEMBE, 2016). This statement links time and space, narrative categories evoked in the concept of Afrofuturism—a cultural, artistic, aesthetic, political, and philosophical movement that centers an Afrocentric vision and Black protagonism, both in reality and in fiction. In the latter, "protagonism" is extensive, as it encompasses both the creation and the creator, asserting a position of prominence in authorship as well as in the construction of characters. In literature, through speculative fiction and its subgenres, this concept allows for reflections on how to build a fairer future and reclaims both space and voice for the Black population. Thus, reality and fiction walk side by side, with literary art stemming from social critique. In this sense, the present work aims to analyze the presence of Afrofuturist aesthetics in Brazilian contemporary literature and other arts, with an emphasis on speculative fiction written by Black authors. More specifically, it investigates the development of the concept of Afrofuturism throughout the history of African-American speculative fiction; examines how Afrofuturism materializes in contemporary Brazilian artistic and literary expressions; studies the representation of Black people in Brazilian science fiction; discusses Afrofuturism as a possible fourth wave of Brazilian science fiction; and, finally, analyzes the literary work of Fábio Kabral and Lu Ain-Zaila through the lens of this concept. It seeks to demonstrate that the Afrofuturist movement, in contemporary Brazilian literature, serves as a means to express the desire for freedom from external perspectives imposed on Black people and their representations, promoting the empowerment and protagonism of this aesthetic. To achieve these goals, we draw upon the critical works of Dery (1994), Womack (2013), and Freitas (2018) on the concept of Afrofuturism; Tavares and Matangrano (2018) and Causo (2003) on the genres of speculative fiction and science fiction in Brazil; and Bernd (1988) and Cuti (2010) on discussions surrounding Black Brazilian literature and related themes. The methodology adopted was textual analysis. It is evident that Afrofuturism marks the emergence of Black Brazilian science fiction and stands as a conquest of voice and space for identity affirmation by a segment of the population that has long been silenced and marginalized.